Are common measures of dietary restraint and disinhibited eating reliable and valid in obese persons?. (1st April 2015) - Bohrer, Brittany K.; Forbush, Kelsie T.; Hunt, Tyler K.
Highlights: We evaluate psychometric properties of common self-report eating disorder measures. Self-report eating disorder measures are valid and reliable among weight groups. Self-report eating disorder measures can be used in obese populations. Abstract: Disordered eating measures were developed and validated in primarily normal weight samples; thus, it is unclear if the psychometric properties are equivalent across weight groups. This study evaluated the reliability and validity of self-reported disinhibited eating and dietary restraint measures in a community-recruited sample of overweight individuals ( N = 201) and obese individuals ( N = 101) and normal weight matched controls. Coefficient alpha and average inter-item correlations were used to test internal consistency reliability. Correlations between lifetime disordered eating behaviors and measures of dietary restraint and disinhibited eating were used to test convergent validity. Disordered eating measures included: Eating Disorders Examination Questionnaire (EDE-Q), Three Factor Eating Questionnaire (TFEQ), Dutch Eating Behavior Questionnaire (DEBQ), Eating Disorders Inventory-3 (EDI-3), and Restraint Scale. Correlations between lifetime disordered eating behaviors and measures of non-disordered-eating-related psychopathology were used to test discriminant validity. Results indicated that most measures demonstrated acceptable internal consistency reliability across groups, with the exception of the Restraint Scale. Significantly higher convergent correlations between lifetime history of fasting and TFEQ Cognitive Restraint emerged for the overweight vs. obese group, and the magnitude of discriminant correlations between lifetime history of binge eating and the Inventory of Depression and Anxiety Symptoms (IDAS) Well Being scale was stronger in the normal weight vs. overweight group. Findings suggest the majority restrained and disinhibited eating measures are reliable and valid among weight groups, and are suitable to use in overweight and obese populations.